Pengaruh Desain dan Inovasi Produk Terhadap Brand Love, Purchase Decision, dan Brand Loyalty Jersey Manchester United - Pengestu, Kantri Setiawan; Tuti, Meylani (Journal of Management and Economics Innovation, 2025)
This study investigates the influence of product design and innovation on brand love, purchase decisions, and brand loyalty among consumers of Manchester United jerseys. Employing a quantitative approach, data were collected from 250 respondents through an online survey and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results reveal that both product design and innovation significantly affect brand love. Furthermore, brand love exerts a strong influence on purchase decisions and brand loyalty. Purchase decisions also have a significant and direct impact on brand loyalty. These findings suggest that emotional attachment, reflected in brand love, plays a pivotal role in shaping consumer behavior, particularly in repeated purchases of identity-related products such as football jerseys. From a practical standpoint, the study highlights the importance for brands to invest in creative design and continuous innovation to foster stronger emotional connections and long-term consumer loyalty.